EVALUATION OF LAND SUITABILITY FOR IRRIGATED WHEAT CULTIVATION USING TWO DIFFERENT METHODS IN NORTHERN ALI AL-GHARBI DISTRICT - A. R. Anbar,; A. I. Hamad, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to evaluate the suitability of land for irrigated wheat cultivation in the Ali Al-Gharbi area in Maysan Governorate.A semi detailed soil survey was conducted covering an area of 77244.66 hectares. 15 pedons were described and 40 surface samples were collected. The study area included three physiographic units: the riverbed unit, the river basin unit, and the depressions unit. Land suitability assessment was conducted following the methodologies outlined by Sys et al., 1993, and the approach proposed by Al-Rubaie )10(. This evaluation encompassed soil characteristics, topography, and irrigation water needs. The results indicated that the determining factor for wheat cultivation is soil salinity and calcium carbonate content. Climate suitability results for wheat cultivation within category S1 reached a rating of (98.8)%, according to the assessment. However, according to the suitability categories outlined by Sys et al., 1993, the unsuitable areas (N2) for cultivation covered an area of 76,336.36 hectares, accounting for 98.82% of the study area, while the suitable category (S1) covered an area of 908.30 hectares, representing 1.18% of the study area. According to the proposal by Al-Rubaie )10(, water availability fell within the limited suitability category S3, with a rating of (66.74)%. The final suitability assessment placed the area within the unsuitable category N1, covering 75,572.73 hectares and representing 97.84% of the study area, and the limited suitability category S3, covering 1,671.93 hectares and representing 2.16% of the study area.